2020
DOI: 10.1093/nutrit/nuaa114
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of oral supplementation with curcumin: a systematic review and meta-analysis of randomized controlled trials

Abstract: Context Chronic inflammation is a major contributor to the development of noncommunicable diseases. Curcumin, a bioactive polyphenol from turmeric, is a well-known anti-inflammatory agent in preclinical research. Clinical evidence remains inconclusive because of discrepancies regarding optimal dosage, duration, and formulation of curcumin. Objective The aim of this systematic review, conducted and reported in accordance with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 65 publications
5
39
1
Order By: Relevance
“…These results are in line with those of other studies which tested the effects of nanocurcumin on Th17 cell-mediated inflammation in other diseases marked by hyper-inflammation or autoimmunity responses, such as multiple sclerosis [50,51], rheumatoid arthritis [52,53], and Alzheimer's disease [54][55][56]. There is also accumulating evidence that curcumin treatment can modulate the cytokine cascade and cytokine storm caused by hyper-production of inflammatory cytokines [57,58]. This property appears to occur through inhibition of nuclear factor (NF)-κB and mitogenactivated protein kinase (MAPK) signaling, which drive cytokine production [15,59,60].…”
Section: Discussionsupporting
confidence: 90%
“…These results are in line with those of other studies which tested the effects of nanocurcumin on Th17 cell-mediated inflammation in other diseases marked by hyper-inflammation or autoimmunity responses, such as multiple sclerosis [50,51], rheumatoid arthritis [52,53], and Alzheimer's disease [54][55][56]. There is also accumulating evidence that curcumin treatment can modulate the cytokine cascade and cytokine storm caused by hyper-production of inflammatory cytokines [57,58]. This property appears to occur through inhibition of nuclear factor (NF)-κB and mitogenactivated protein kinase (MAPK) signaling, which drive cytokine production [15,59,60].…”
Section: Discussionsupporting
confidence: 90%
“…Polyphenols are plant secondary metabolites, which, in the last decades, attracted the attention of the scientific community due to their health properties. Several epidemiological studies and meta-analyses strongly suggest that long-term consumption of diets rich in plant polyphenols offer protection against development of cancers, cardiovascular diseases, diabetes, osteoporosis and neurodegenerative diseases [13][14][15][16][17]. A major source of polyphenols (40-1000 mg/kg) is represented by extra virgin olive oil (EVOO), whose phenolic fraction includes simple phenols (tyrosol and hydroxytyrosol), secoiridoids (oleuropein, oleocanthal and oleacein) and lignans [18].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, several authors reported clinical benefits of a curcumin supplementation on main functional parameters related to prostatic diseases [26,27], such as pain relief [27]. Curcumin, a bioactive polyphenol from turmeric, is a common anti-inflammatory agent in preclinical research, and a recent systematic review demonstrated its anti-inflammatory effects, suggesting further investigations to confirm dose, duration and formulation to optimize its implementation in urological practice for chronic inflammation of the lower urinary tract [28]. Finally, several authors showed the beneficial effects of soybean extracts (glycine max) on the prostate physiology [29], as well as the benefits of pinus pinaster [30].…”
Section: Results In Comparison With Other Studiesmentioning
confidence: 96%